Legislation meets science : implementing a macroalgae farm to reach the requirements of the Water Framework Directive - Vidal, Lisa Christine, 1988- (2019)
Verkefnið er lokað til 15.06.2020. The EU Water Framework Directive obliges its Member States to reach good ecological and chemical status of all inland water bodies within a timeframe of fifteen years. According to the decision 125/2007 of the EEA Joint Committee, also Iceland is required to achieve such goals by the year 2022. Due to reduced governmental budget, the implementation process within Iceland stagnated and just recently started again. Nutrient excess and the potential risk of eutrophication, primarily caused by anthropogenic activities, is one major threat for Icelandic marine and freshwater bodies. This thesis aimed to observe whether the nutrient absorption potential of macroalgae could be applied as a supportive measure to improve marine water quality and, thus, to achieve the requirement under the Water Framework Directive. First, specific challenges regarding the national implementation of the Directive were explored. The second part of the study involved the installation and observation of a local and small-scale trial farm with different native algae within the inner fjord of Ísafjörður, Iceland. Contrary to expectations, algal biomass could not be reached which was potentially caused by the fluctuation of several physical parameters and threat due to grazers and epiphytic biofouling. The construction could not withstand the local weather conditions during winter. The results of a preliminary analysis based on peer-reviewed data show that the brown algae species Laminaria digitata might be most suited to absorb the majority of nutrients. Macroalgae farming might not replace proper sewage treatment systems at the study site due to the overload of nutrients, but could be applied as additive measure for improving the water quality. Future research should focus on the application of different cultivation methods and designs as well as cost-benefit-analyses.